Isolated internal jugular and subclavian vein thrombosis: a rare complication of pancreatitis. A case report - Atif , Qurrat Al Ain; Adel Hamed (Journal of the Pakistan Medical Association, 2022)
Splanchnic vein thromboses are well recognized vascular complications of acute as well as chronic pancreatitis. Extra splanchnic thromboses have rarely been reported. One such case of a 41-year-old Pakistani male patient who developed acute alcoholic pancreatitis is presented. On further workup he was found to have bilateral internal jugular and subclavian vein thrombosis with patent splanchnic veins. Pancreatitis generally creates a procoagulant state in the body. Moreover, the inflammatory process itself along with compression from peri-pancreatic fluid collections cause injury to the nearby vessels resulting in vascular complications. Whether venous or arterial, vascular complications of acute or chronic pancreatitis have fatal consequences. Extra splanchnic venous thromboses do occur and should be sought for, if symptoms indicate. Internal jugular and subclavian vein thrombosis can lead to pulmonary embolism and mortality. Hence appropriate timely diagnosis and effective treatment should be commenced to avoid any untoward consequences. Keywords: pancreatitis, splanchnic vein thrombosis, extra splanchnic vein thrombosis, pancreatic pseudocyst. Continue...